RIPK1 inhibition in malignant cells potentiates immunotherapy and radiotherapy outcome - Jonathan G. Pol; Andrea Checcoli; Manuela Lizarralde-Guerrero; Guido Kroemer (OncoImmunology, 2024)
Apoptosis, necroptosis and pro-inflammatory NF-κB-dependent signaling are repressed by receptor-interacting serine/threonine-protein kinase 1 (RIPK1). A recent paper in Immunity describes a small molecule inducing the proteolytic degradation of RIPK1. In preclinical experiments, this RIPK1 inhibitor improved the anticancer efficacy of radiotherapy, immunotherapy (with PD-1 blockade) and radioimmunotherapy (with CTLA-4 blockade).